2015
DOI: 10.1063/1.4915288
|View full text |Cite
|
Sign up to set email alerts
|

Wind potential evaluation around isolated pitched roof buildings

Abstract: The knowledge of wind field characteristics around buildings is very useful in a variety of applications such as energy supply by means of a domestic wind turbine. In this paper, results of a wind study around a conventional pitched roof building are given in order to choose the best location and therefore to maximize a micro-wind turbine production. Numerical results on a bluff body (cube) have been performed by means of computational fluid dynamics techniques and the Reynolds Averaged Navier-Stokes approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Sedaghat [5] concluded that the Magnus wind turbine power coefficient is not as yet promising for urban environments, which includes highly variable flow direction, low speeds and high shear [6]. To improve this performance, local configurations may be considered as proposed by Bourabaa et al [7].…”
Section: Nomenclature Amentioning
confidence: 99%
“…Sedaghat [5] concluded that the Magnus wind turbine power coefficient is not as yet promising for urban environments, which includes highly variable flow direction, low speeds and high shear [6]. To improve this performance, local configurations may be considered as proposed by Bourabaa et al [7].…”
Section: Nomenclature Amentioning
confidence: 99%
“…However, in spite of its specific features, very limited research work has been carried out in this specific area of wind load on pyramidal roof buildings (Roy et al 2018b;Roy et al 2018a). Maximum studies in this field are concerned with low-rise buildings with canopy roof (Roy 2010, a) gable roof, hip roof (Ahmad and Kumar 2001;Irtaza et al 2015;Tecle et al 2015;Habte et al 2017), isolated pitched roof (Bourabaa et al 2015), tall chimney (Verma et al 2015;Khan and Roy 2017) and tall structures (Paul and Dalui 2008;Amin and Ahuja 2014;Kar and Dalui 2016;P. Martinez-Vazquez 2016;Sanyal and Kumar 2018), and aim to provide information about the consistency of performance and the upgrading of design economy (Isyumov 1999).…”
Section: Introductionmentioning
confidence: 99%